Early viscous fluid cosmological model with zero-rest-mass scalar fields - Ram S.; Singh C.P. (My University, 2025)
Einstein field equations are considered for zero-curvature Robertson-Walker models in the case of a viscous fluid distribution interacting with zero-rest-mass scalar fields. Exact solutions are obtained for two different phases of the early universe viz. the inflationary phase and the radiation-dominated phase, by using the 'gamma-law' equation of state p = (γ - 1)ρ. The γ index describing the material content varies continuously with cosmological time. The gravitational 'constant' and bulk viscosity are both allowed to depend on the cosmic time. Some physical properties of the cosmological models are also discussed.